Investigation of intracellular signals generated by γ-interferon and IL-4 leading to the induction of class II antigen expression - S. Vassiliadis; N. Kyrpides; D. Stravopodis; M. Grigoriou; I. Athanassakis; J. Papamatheakis (Mediators of Inflammation)
Signal transduction plays a vital role in cellular behaviour as cells respond to various stimuli in different ways and utilize diverse pathways for accomplishing their task. Determination of the pathway followed by various cytokines can be achieved using specific inhibitors which include theophylline (TPH), TMB-8 and W7 that hinder calmodulin binding to Ca2+; sphingosine (SPH), H7 and staurosporine that inhibit protein kinase C (PKC) activation; and mevalonate (MEV) or the anti-p21ras antibody which block G-proteins. This study shows that the immunologically important class II antigens in human cells are up-regulated predominately via the same pathway after gamma-interferon (γ-IFN) treatment, whereas murine cells are activated by other signalling routes. Thus, the calcium/calmodulin (Ca2+/Cam) pathway is preferentially selected for human cells whereas the PKC pathway is more often chosen for murine cells. These findings are firmly supported by other reports and show, in addition, a unique action exerted by γ-IFN, since IL-4, another inducer of class II antigen expression, uses different pathways. This diversity of activation reveals the existence of a previously unknown complicated network of intracellular interactions able to regulate the same phenotype or cellular event. As major histocompatibility complex antigens (MHC) or human leukocyte antigens (HLA), are important in immune recognition and response, the results show that for human cells a more coherent method of HLA-DR antigen induction is followed after γ-IFN administration, as calcium participation seems to be the first step in signal transduction. The same T-cell derived lymphokine, however, follows a totally different route when applied to murine cells.